Tahap Asimilasi Etnik : Kajian Kes Melayu Dan Cina Di Kelantan - Karim, Mohamad Sukor Abdul (2012)
This thesis aims to examine and analyse the ethnic relationship with focusing the level of assimilation of Kelantanese’s Chinese in Kelantan. To obtain it, a field work has been done throughout questionnaire. Main objective of this study is to measure the level of assimilation of the Chinese ethnic who live in Kelantan. Furthermore to attain the objective, 200 respondents have been selected among two majors ethnic which it Chinese and Malay. In line with that, a scale of measurement has been constructed as a tool (instrument) to quantify the level of Chinese ethnic assimilation according to three variables based on perception, behaviour and stereotype. The finding revealed that the stage of assimilation of the Chinese ethnic in Kelantan is at a level “extra assimilation”. Overall, this study has achieved the objective, and reflects the exact minority ethnic level of assimilation in Kelantan.